A novel numerical method for accelerating the computation of the steady-state in induction machines. (15th January 2020) - Bermúdez, A.; Gómez, D.; Piñeiro, M.; Salgado, P.
Abstract: This paper presents a novel and efficient methodology to reduce the time needed to reach the steady-state in the finite element simulation of induction machines. More precisely, the work focuses on induction motors with squirrel cage rotor, where sources in the stator coil sides are given in terms of periodic currents. Essentially, the procedure consists in computing suitable initial conditions for the currents in the rotor bars, thus allowing to obtain the steady-state fields of the machine by solving a transient magnetic model in just a few revolutions. Firstly, the mathematical model that simulates the behavior of the machine is introduced. Then, an approximation of this model is developed, from which suitable initial currents are derived by computing the solution in the least-square sense to an overdetermined problem with only two unknowns. Finally, the method is applied to a particular induction machine working under different operating conditions. The results show important computational savings to reach the motor steady-state in comparison with assuming zero initial conditions, which validate the efficiency of the procedure.